Long-term Radio Monitoring of the Fast X-Ray Transient EP 240315a: Evidence for a Relativistic Jet - Ricci, Roberto; Troja, Eleonora; Yang, Yu-Han; Yadav, Muskan; Liu, Yuan; Sun, Hui; Wu, Xuefeng; Gao, He; Zhang, Bing; Yuan, Weimin (Astrophysical journal. Letters, 2025)
The recent launch of Einstein Probe (EP) in early 2024 opened up a new window onto the transient X-ray sky, allowing for real-time discovery and follow-up of fast X-ray transients (FXRTs). Multiwavelength observations of FXRTs and their counterparts are key to characterize the properties of their outflows and, ultimately, identify their progenitors. Here, we report our long-term radio monitoring of EP 240315A, a long-lasting (∼1000 s) high-redshift ( z = 4.9) FXRT associated to gamma-ray burst (GRB) 240315C. Our campaign, carried out with the Australian Telescope Compact Array, followed the transient’s evolution at two different frequencies (5.5 and 9 GHz) for 3 months. In the radio light curves we identify an unusual steep rise at 9 GHz, possibly due to a refreshed reverse shock, and a late-time rapid decay of the radio flux, which we interpret as a jet break due to the outflow collimation. We find that the multiwavelength counterpart of EP 240315A is well described by a model of relativistic jet seen close to its axis, with jet half-opening angle θ j ≈ 3° and beaming-corrected total energy E ≃ 4 × 10 51 erg, typical of GRBs. These results show that a substantial fraction of FXRTs may be associated to standard GRBs and that sensitive X-ray monitors, such as EP and the proposed HiZ-GUNDAM and Theseus missions, can successfully pinpoint their relativistic outflows up to high redshifts.